HOW YOUNG ENGLISH TEACHERS, WHO RECENTLY STARTED THEIR CAREER, CAPTURED INTERESTS OF SCHOOL STUDENTS INTO LESSON PROCESS. - Aktamova Zarnigor Yahyo qizi; Yusupova Muhabbat Anatolevna (Ta'lim innovatsiyasi va integratsiyasi, 2024)
ABSTRACT This article is useful for young teachers who have recently started their careers and young people studying in the field of pedagogy, because there are a lot of necessary information and methods. This article analyzes the methods necessary for school children and students to focus on the subject being taught and to fully master the subject, rather than looking at the clock while waiting for the end of the lesson.